Cooling liquid and application thereof in immersed liquid cooling system
By adopting a specific formula coolant, the shortcomings of the existing coolant in terms of thermal conductivity, anti-rust ability and chemical stability are solved, and high thermal conductivity, good anti-rust performance and chemical stability are achieved, and it is suitable for immersed liquid cooling systems.
Patent Information
- Application Number
- CN202510084624.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-29
AI Technical Summary
The existing coolant has shortcomings in thermal conductivity, anti-rust ability, chemical stability, corrosion to materials and environmental friendliness, and it is difficult to meet the growing heat dissipation needs and increasingly stringent environmental protection standards.
A coolant composed of propylene glycol, synthetic oil, anti-rust agent, solubilizer, antioxidant, functional additive and thermal filler is used to improve its thermal conductivity, anti-rust properties and chemical stability through specific formula ratios and preparation methods.
The coolant with high thermal conductivity, good chemical stability and rust resistance and low viscosity can effectively reduce the impact of external corrosion factors on metals, improve the stability and safety of the coolant, and also has excellent thermal conductivity and high flash point.
Smart Images

Figure BDA0005249750420000121
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of cooling liquids, and in particular relates to a cooling liquid and an application thereof in an immersion liquid cooling system. Background Art
[0002] Coolant is a multifunctional liquid that can prevent freezing in winter, avoid boiling in summer, and effectively prevent scale formation all year round due to its unique chemical composition and physical and chemical properties. It is a mixture of various substances designed to lower the freezing point of the system, enhance heat exchange efficiency, and protect metal parts from corrosion. With the rapid advancement of electronic technology, the power density of electronic devices such as servers and high-performance computers continues to rise. If the large amount of heat generated by these devices during operation cannot be quickly and effectively discharged, it will seriously threaten their performance and operating stability, and in extreme cases may even cause equipment damage. Immersion liquid cooling system has emerged as an efficient heat dissipation solution. However, the coolants currently used have deficiencies in many aspects, such as thermal conductivity, rust resistance, chemical stability, corrosiveness to materials, and environmental friendliness, and it is difficult to fully meet the growing heat dissipation needs and increasingly stringent environmental protection standards. Therefore, it is particularly urgent and important to develop a new type of coolant to solve existing problems and meet future development needs. Summary of the invention
[0003] In view of the deficiencies in the prior art, the present invention provides a coolant for an immersion liquid cooling system with high thermal conductivity, good chemical stability and rust resistance, and low viscosity.
[0004] To solve the above problems, the technical solution adopted by the present invention is:
[0005] A coolant comprising the following raw materials in parts by weight:
[0006] 60-70 parts of propylene glycol, 15-25 parts of synthetic oil, 3-6 parts of rust inhibitor, 0.5-1 part of solubilizer, 0.2-0.5 part of antioxidant, 0.3-0.6 part of functional additive, 1.5-2.5 parts of thermal conductive filler.
[0007] Preferably, the rust inhibitor is prepared by compounding the functional product, myrcene imidazoline and triethyl borate in a mass ratio of 3-5:0.8-1.2:0.2-0.4.
[0008] Preferably, the functional product is prepared by the following method:
[0009] A1, dispersing tert-butyldiphenylchlorosilane and pyridine in toluene, adding eugenol, stirring for 25-35 minutes, and distilling under reduced pressure to obtain an intermediate product 1; wherein the mass ratio of tert-butyldiphenylchlorosilane, pyridine, toluene and eugenol is 0.5-0.8:0.02-0.05:30-35:1-2;
[0010] A2, N-bromosuccinimide and dimethylformamide are mixed, then benzoyl peroxide is added, stirred for 1-2h, intermediate product 1 is added, heated with stirring for 2-4h, then isopropanolamine is added, heated with stirring for 60-80min, then L-cysteic acid is added, heated with stirring for 2-3h, and distilled under reduced pressure to obtain intermediate product 2; wherein, the mass ratio of N-bromosuccinimide, dimethylformamide, benzoyl peroxide, intermediate product 1, isopropanolamine and L-cysteic acid is 15-25:130-150:1-2:30-40:20-25:10-15;
[0011] A3. Mix the intermediate product 2 with the tetrahydrofuran solution, stir for 10-15 min, add tetrabutylammonium fluoride, heat and stir for 25-40 min, and distill under reduced pressure to obtain a functional product; wherein the mass ratio of the intermediate product 2, the tetrahydrofuran solution and the tetrabutylammonium fluoride is 10-15:50-60:2-4.
[0012] Preferably, the functional additive is prepared by mixing polydimethylsiloxane and a diesel flash point enhancer in a mass ratio of 0.5-0.8:4-5.
[0013] Preferably, the thermally conductive filler is prepared by the following method:
[0014] The graphene oxide is dispersed in deionized water, ultrasonically dispersed for 15-25 minutes, zinc acetate and p-phenylenediamine are added, stirred for 5-8 minutes, sodium hydroxide is added to adjust the pH to obtain a mixed solution, the mixed solution is heated to 150-180° C., kept warm for 12-20 hours, cooled to room temperature, centrifuged, washed, and dried to obtain a thermal conductive filler.
[0015] Preferably, the mass ratio of the graphene oxide, zinc acetate, p-phenylenediamine, sodium hydroxide and deionized water is 8-12:2-4:0.5-0.8:0.05-0.1:60-75.
[0016] A method for preparing a coolant comprises the following steps:
[0017] The antioxidant, functional additive, thermal conductive filler and propylene glycol are mixed, and then synthetic oil and rust inhibitor are added, stirred for 25-35 minutes, and then a solubilizer is added, and stirred for 30-45 minutes to prepare a coolant.
[0018] Preferably, the antioxidant is at least one of 2,6-di-tert-butyl-4-methylphenol, triethylene glycol bis[3-(3-tert-butyl-5-methyl-4-hydroxyphenyl) propionate] and di(2-methyl-5-tert-butyl-4-hydroxyphenyl) sulfide.
[0019] Preferably, the solubilizer is at least one of alkylphenol polyoxyethylene ether OP-10, sodium lauryl sulfate and triethanolamine oleate DX1898.
[0020] The invention also provides application of the cooling liquid in an immersion cooling system.
[0021] In summary, the present invention has the following beneficial effects:
[0022] The present invention allows tert-butyldiphenylchlorosilane and eugenol to react to obtain an intermediate product 1, then N-bromosuccinimide, benzoyl peroxide and the intermediate product 1 are mixed for reaction, isopropanolamine is added for stirring, and finally L-sulfoalanine is added to obtain an intermediate product 2, which is then reacted with tetrabutylammonium fluoride to obtain a functional product. The functional product contains a plurality of active functional groups, such as a phenolic hydroxyl group, an amino group, and a sulfonic acid group. The sulfonic acid group can chemically adsorb on a metal surface to provide rust prevention protection, and the presence of the phenolic hydroxyl group can form a polymer film with a certain protective ability, effectively blocking the invasion of external corrosive substances, and while playing an anti-rust role, it can also capture free radicals, inhibit the progress of oxidation reactions, and help maintain the coolant. In addition, the long-chain structure of lauric acid imidazoline can provide steric hindrance to prevent the corrosive medium from approaching the metal surface. The imidazoline ring can be adsorbed on the metal surface and the pH value of the anti-rust system can be regulated. The amino group in the functional product interacts with the imidazoline ring of myrcene imidazoline to enhance the adsorption capacity on the metal surface. The boric acid after hydrolysis of triethyl borate can undergo condensation reaction with the hydroxyl and amino groups in the functional product to form a denser protective film on the metal surface. The functional product can also provide a suitable microenvironment for the hydrolysis of boric acid and the formation of a protective film, thereby promoting triethyl borate to play a better anti-rust role. The synergistic effect of the functional product, myrcene imidazoline and triethyl borate can jointly promote the anti-rust effect of the coolant.
[0023] The invention mixes graphene oxide, zinc acetate and p-phenylenediamine, and obtains a thermal conductive filler after heating and stirring. The p-phenylenediamine is introduced to undergo an amidation reaction with a functional group on the surface of the graphene oxide, thereby modifying the graphene oxide and preventing the graphene oxides from agglomerating, thereby improving the dispersibility of the graphene oxide. The zinc ions are introduced to form a coordination bond with the graphene oxide, thereby changing the microstructure of the graphene and participating in the construction of a new chemical bond network in a subsequent heating process, thereby enhancing the thermal conductivity. The p-phenylenediamine and the zinc ions exhibit a synergistic effect, and the two can interact with the functional groups on the surface of the graphene oxide together, thereby reducing the erosion of the graphene oxide by external chemical substances by forming a more stable chemical bond, and optimizing the heat conduction path, thereby improving the thermal conductivity. DETAILED DESCRIPTION
[0024] The present invention will be further described below in conjunction with specific embodiments, but the embodiments do not limit the present invention in any form.
[0025] Synthetic oil, purchased from Shenzhen Huamite Lubrication Technology Co., Ltd., product model: base oil 500N; alkylphenol polyoxyethylene ether OP-10, purchased from Jinan Yuanlian Chemical Co., Ltd.; triethanolamine oleate DX1898, purchased from Dexu New Materials (Guangzhou) Co., Ltd.; 2,6-di-tert-butyl-4-methylphenol, purchased from Zhengzhou Alpha Chemical Co., Ltd.; triethylene glycol bis[3-(3-tert-butyl-5-methyl-4-hydroxyphenyl) propionate], purchased from Tianjin Lianlong New Materials Co., Ltd. ; Di(2-methyl-5-tert-butyl-4-hydroxyphenyl) sulfide, purchased from Guangdong Wengjiang Chemical Reagent Co., Ltd.; tert-butyldiphenylchlorosilane, purchased from Hubei Jiangmin Taihua Chemical Co., Ltd.; eugenol, purchased from Jiangxi Xinsen Natural Vegetable Oil Co., Ltd.; L-sulfoalanine, purchased from Wuhan Xinxin Jiali Biotechnology Co., Ltd.; diesel flash point enhancer, purchased from Hubei Xinghengye Technology Co., Ltd., graphene oxide, No. XF022-1, Article No.: 102066, purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.
[0026] Example 1
[0027] A coolant comprising the following raw materials in parts by weight:
[0028] 60 parts of propylene glycol, 15 parts of synthetic oil, 3 parts of rust inhibitor, 0.5 parts of solubilizer, 0.2 parts of antioxidant, 0.3 parts of functional additive, and 1.5 parts of thermal conductive filler.
[0029] The rust inhibitor is prepared by compounding the functional product, myrcene imidazoline and triethyl borate in a mass ratio of 3:0.8:0.2.
[0030] Wherein, the functional product is prepared by the following method:
[0031] A1, dispersing tert-butyldiphenylchlorosilane and pyridine in toluene, stirring at 100 rpm for 10 min, adding eugenol, stirring at 100 rpm for 25 min, and distilling under reduced pressure to obtain an intermediate product 1; wherein the mass ratio of tert-butyldiphenylchlorosilane, pyridine, toluene and eugenol is 0.5:0.02:30:1;
[0032] A2, N-bromosuccinimide and dimethylformamide were mixed, stirred at 100rpm for 8min, benzoyl peroxide was added, stirred at 80rpm for 1h, intermediate product 1 was added, stirred at 40°C and 100rpm for 2h, isopropanolamine was added, stirred at 45°C and 100rpm for 60min, L-cysteic acid was added, stirred at 50°C and 100rpm for 2h, and distilled under reduced pressure to obtain intermediate product 2; wherein the mass ratio of N-bromosuccinimide, dimethylformamide, benzoyl peroxide, intermediate product 1, isopropanolamine and L-cysteic acid was 15:130:1:30:20:10;
[0033] A3. Mix the intermediate product 2 with the tetrahydrofuran solution, stir at 100 rpm for 10 min, add tetrabutylammonium fluoride, stir at 30° C. and 120 rpm for 25 min, and distill under reduced pressure to obtain a functional product; wherein the mass ratio of the intermediate product 2, the tetrahydrofuran solution and the tetrabutylammonium fluoride is 10:50:2.
[0034] The functional additive is prepared by mixing polydimethylsiloxane and a diesel flash point enhancer in a mass ratio of 0.5:4.
[0035] Wherein, the thermal conductive filler is prepared by the following method:
[0036] The graphene oxide was dispersed in deionized water, ultrasonically dispersed at 25kHz for 15 minutes, zinc acetate and p-phenylenediamine were added, stirred at 80rpm for 5 minutes, sodium hydroxide was added to adjust the pH to 10 to obtain a mixed solution, the mixed solution was heated to 150°C, kept stirring for 12 hours, the stirring rate was controlled to be 150rpm, cooled to room temperature, centrifuged at 6000rpm for 5 minutes, washed with ethanol 4 times, and dried at 70°C for 8 hours to obtain a thermal conductive filler; wherein the mass ratio of graphene oxide, zinc acetate, p-phenylenediamine, sodium hydroxide and deionized water is 8:2:0.5:0.05:60.
[0037] A method for preparing a coolant comprises the following steps:
[0038] The antioxidant, functional additive, thermal conductive filler and propylene glycol are mixed, stirred at 100 rpm for 15 minutes, then synthetic oil and rust inhibitor are added, stirred at 120 rpm for 25 minutes, then a solubilizer is added, and stirred at 200 rpm for 30 minutes to prepare a coolant; wherein the antioxidant is 2,6-di-tert-butyl-4-methylphenol; and the solubilizer is alkylphenol polyoxyethylene ether OP-10.
[0039] Example 2
[0040] A coolant comprising the following raw materials in parts by weight:
[0041] 70 parts of propylene glycol, 25 parts of synthetic oil, 6 parts of rust inhibitor, 1 part of solubilizer, 0.5 parts of antioxidant, 0.6 parts of functional additive, and 2.5 parts of thermal conductive filler.
[0042] The rust inhibitor is prepared by compounding the functional product, myrcene imidazoline and triethyl borate in a mass ratio of 5:1.2:0.4.
[0043] Wherein, the functional product is prepared by the following method:
[0044] A1, dispersing tert-butyldiphenylchlorosilane and pyridine in toluene, stirring at 200 rpm for 15 min, adding eugenol, stirring at 200 rpm for 35 min, and distilling under reduced pressure to obtain an intermediate product 1; wherein the mass ratio of tert-butyldiphenylchlorosilane, pyridine, toluene and eugenol is 0.8:0.05:35:2;
[0045] A2, N-bromosuccinimide and dimethylformamide were mixed, stirred at 200rpm for 12min, benzoyl peroxide was added, stirred at 8120rpm for 2h, intermediate product 1 was added, stirred at 50°C and 200rpm for 4h, isopropanolamine was added, stirred at 55°C and 150rpm for 80min, L-cysteic acid was added, stirred at 60°C and 200rpm for 3h, and distilled under reduced pressure to obtain intermediate product 2; wherein the mass ratio of N-bromosuccinimide, dimethylformamide, benzoyl peroxide, intermediate product 1, isopropanolamine and L-cysteic acid is 25:150:2:40:25:15;
[0046] A3. Mix the intermediate product 2 with the tetrahydrofuran solution, stir at 150 rpm for 15 min, add tetrabutylammonium fluoride, stir at 40° C. and 160 rpm for 40 min, and distill under reduced pressure to obtain a functional product; wherein the mass ratio of the intermediate product 2, the tetrahydrofuran solution and the tetrabutylammonium fluoride is 15:60:4.
[0047] The functional additive is prepared by mixing polydimethylsiloxane and diesel flash point enhancer in a mass ratio of 0.8:5.
[0048] Wherein, the thermal conductive filler is prepared by the following method:
[0049] The graphene oxide was dispersed in deionized water, ultrasonically dispersed at 35kHz for 25 minutes, zinc acetate and p-phenylenediamine were added, stirred at 100rpm for 8 minutes, sodium hydroxide was added to adjust the pH to 12 to obtain a mixed solution, the mixed solution was heated to 180°C, kept stirred for 20 hours, the stirring rate was controlled to be 200rpm, cooled to room temperature, centrifuged at 8000rpm for 7 minutes, washed with ethanol 6 times, and dried at 90°C for 12 hours to obtain a thermal conductive filler; wherein the mass ratio of graphene oxide, zinc acetate, p-phenylenediamine, sodium hydroxide and deionized water is 12:4:0.8:0.1:75.
[0050] A method for preparing a coolant comprises the following steps:
[0051] The antioxidant, functional additive, thermal conductive filler and propylene glycol were mixed, stirred at 200 rpm for 25 minutes, then synthetic oil and rust inhibitor were added, stirred at 150 rpm for 35 minutes, then a solubilizer was added, and stirred at 300 rpm for 45 minutes to prepare a coolant; wherein the antioxidant was triethylene glycol bis[3-(3-tert-butyl-5-methyl-4-hydroxyphenyl) propionate]; and the solubilizer was sodium dodecyl sulfate.
[0052] Example 3
[0053] A coolant comprising the following raw materials in parts by weight:
[0054] 65 parts of propylene glycol, 20 parts of synthetic oil, 5 parts of rust inhibitor, 0.8 parts of solubilizer, 0.5 parts of antioxidant, 0.5 parts of functional additive, and 2 parts of thermal conductive filler.
[0055] The rust inhibitor is prepared by compounding the functional product, myrcene imidazoline and triethyl borate in a mass ratio of 4:1:0.3.
[0056] Wherein, the functional product is prepared by the following method:
[0057] A1, dispersing tert-butyldiphenylchlorosilane and pyridine in toluene, stirring at 150 rpm for 13 min, adding eugenol, stirring at 150 rpm for 30 min, and distilling under reduced pressure to obtain an intermediate product 1; wherein the mass ratio of tert-butyldiphenylchlorosilane, pyridine, toluene and eugenol is 0.7:0.04:33:1.5;
[0058] A2, N-bromosuccinimide and dimethylformamide were mixed, stirred at 150rpm for 10min, benzoyl peroxide was added, stirred at 100rpm for 1.5h, intermediate product 1 was added, stirred at 45°C and 150rpm for 3h, isopropanolamine was added, stirred at 50°C and 130rpm for 70min, L-cysteic acid was added, stirred at 55°C and 150rpm for 2.5h, and distilled under reduced pressure to obtain intermediate product 2; wherein the mass ratio of N-bromosuccinimide, dimethylformamide, benzoyl peroxide, intermediate product 1, isopropanolamine and L-cysteic acid is 20:140:1.5:35:23:12;
[0059] A3. Mix the intermediate product 2 with the tetrahydrofuran solution, stir at 130 rpm for 12 min, add tetrabutylammonium fluoride, stir at 35° C. and 140 rpm for 35 min, and distill under reduced pressure to obtain a functional product; wherein the mass ratio of the intermediate product 2, the tetrahydrofuran solution and the tetrabutylammonium fluoride is 13:55:3.
[0060] The functional additive is prepared by mixing polydimethylsiloxane and diesel flash point enhancer in a mass ratio of 0.7:4.5.
[0061] Wherein, the thermal conductive filler is prepared by the following method:
[0062] The graphene oxide was dispersed in deionized water, ultrasonically dispersed at 30kHz for 20 minutes, zinc acetate and p-phenylenediamine were added, stirred at 90rpm for 7 minutes, sodium hydroxide was added to adjust the pH to 11 to obtain a mixed solution, the mixed solution was heated to 170°C, kept stirring for 16 hours, the stirring rate was controlled to be 180rpm, cooled to room temperature, centrifuged at 7000rpm for 6 minutes, washed with ethanol 5 times, and dried at 80°C for 10 hours to obtain a thermal conductive filler; wherein the mass ratio of graphene oxide, zinc acetate, p-phenylenediamine, sodium hydroxide and deionized water is 10:3:0.7:0.08:68.
[0063] A method for preparing a coolant comprises the following steps:
[0064] An antioxidant, a functional additive, a thermal conductive filler and propylene glycol were mixed, stirred at 150 rpm for 20 minutes, and then synthetic oil and a rust inhibitor were added, stirred at 140 rpm for 30 minutes, and then a solubilizer was added, and stirred at 250 rpm for 35 minutes to prepare a coolant; wherein the antioxidant was di(2-methyl-5-tert-butyl-4-hydroxyphenyl) sulfide; and the solubilizer was triethanolamine oleate DX1898.
[0065] Comparative Example 1
[0066] Comparative Example 1 is the same as Example 1, except that the rust inhibitor is prepared by mixing the functional product and myrcene imidazoline in a mass ratio of 3:0.8.
[0067] Comparative Example 2
[0068] Comparative Example 2 is the same as Example 1, except that the rust inhibitor is prepared by mixing the functional product and triethyl borate in a mass ratio of 3:0.2.
[0069] Comparative Example 3
[0070] Comparative Example 3 is the same as Example 1, except that the rust inhibitor is prepared by mixing myrcene imidazoline and triethyl borate in a mass ratio of 0.8:0.2.
[0071] Comparative Example 4
[0072] Comparative Example 4 is the same as Example 1, except that the preparation method of the thermal conductive filler is different, as follows:
[0073] The thermal conductive filler is prepared by the following method:
[0074] The graphene oxide was dispersed in deionized water, ultrasonically dispersed at 25kHz for 15 minutes, p-phenylenediamine was added, stirred at 80rpm for 5 minutes, sodium hydroxide was added to adjust the pH to 10 to obtain a mixed solution, the mixed solution was heated to 150°C, kept stirring for 12 hours, the stirring rate was controlled to be 150rpm, cooled to room temperature, centrifuged at 6000rpm for 5 minutes, washed with ethanol 4 times, and dried at 70°C for 8 hours to obtain a thermal conductive filler; wherein the mass ratio of graphene oxide, p-phenylenediamine, sodium hydroxide and deionized water is 8:0.5:0.05:60.
[0075] Comparative Example 5
[0076] Comparative Example 5 is the same as Example 1, except that the preparation method of the thermal conductive filler is different, as follows:
[0077] The thermal conductive filler is prepared by the following method:
[0078] The graphene oxide was dispersed in deionized water, ultrasonically dispersed at 25 kHz for 15 minutes, zinc acetate was added, stirred at 80 rpm for 5 minutes, sodium hydroxide was added to adjust the pH to 10 to obtain a mixed solution, the mixed solution was heated to 150°C, kept stirred for 12 hours, the stirring rate was controlled to be 150 rpm, cooled to room temperature, centrifuged at 6000 rpm for 5 minutes, washed with ethanol 4 times, and dried at 70°C for 8 hours to obtain a thermal conductive filler; wherein the mass ratio of graphene oxide, zinc acetate, sodium hydroxide and deionized water is 8:2:0.05:60.
[0079] Comparative Example 6
[0080] Comparative Example 6 is the same as Example 1, except that the preparation method of the functional product is different, as follows:
[0081] The functional product was prepared by the following method:
[0082] N-bromosuccinimide and dimethylformamide are mixed, stirred at 100 rpm for 8 minutes, benzoyl peroxide is added, stirred at 80 rpm for 1 hour, eugenol is added, stirred at 40°C and 100 rpm for 2 hours, isopropanolamine is added, stirred at 45°C and 100 rpm for 60 minutes, L-sulfoalanine is added, stirred at 50°C and 100 rpm for 2 hours, and distilled under reduced pressure to obtain a functional product; wherein the mass ratio of N-bromosuccinimide, dimethylformamide, benzoyl peroxide, eugenol, isopropanolamine and L-sulfoalanine is 15:130:1:30:20:10.
[0083] Performance Testing
[0084] The following performance tests were performed on the coolants obtained in Examples 1-3 and Comparative Examples 1-6:
[0085] Thermal conductivity: Performance test is carried out in accordance with ASTM D7896;
[0086] Aging performance test: at 60℃, the use time is 7d;
[0087] Anti-rust performance: tested according to SH / T0085-1991 engine coolant corrosion test method;
[0088] Flash point: Tested in accordance with GB / T3536.
[0089] Table 1 Performance indicators of coolant
[0090]
[0091] It can be seen from the test data in Table 1 that the coolant provided by the present invention has a higher flash point and exhibits a higher thermal conductivity, and can transfer energy efficiently and quickly; from the perspective of anti-rust performance, the coolant can effectively reduce the impact of external corrosion factors on metals; in summary, the coolant prepared by the present invention has excellent anti-rust performance, excellent thermal conductivity and a higher flash point, and at the same time, the preparation process is simple and the comprehensive cost is excellent.
[0092] This specific embodiment is merely an explanation of the present invention and is not a limitation of the present invention. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed. However, as long as they are within the scope of the claims of the present invention, they are protected by the patent law.
Claims
1. A cooling liquid, characterized in that: The invention comprises the following raw materials in parts by weight: 60-70 parts of propylene glycol, 15-25 parts of synthetic oil, 3-6 parts of rust inhibitor, 0.5-1 part of solubilizer, 0.2-0.5 part of antioxidant, 0.3-0.6 part of functional additive, 1.5-2.5 parts of thermal conductive filler.
2. The coolant according to claim 1, characterized in that: The rust inhibitor is prepared by compounding a functional product, myrcene imidazoline and triethyl borate in a mass ratio of 3-5:0.8-1.2:0.2-0.
4.
3. The coolant according to claim 2, characterized in that: The functional product is prepared by the following method: A1, dispersing tert-butyldiphenylchlorosilane and pyridine in toluene, adding eugenol, stirring for 25-35 minutes, and distilling under reduced pressure to obtain an intermediate product 1; wherein the mass ratio of tert-butyldiphenylchlorosilane, pyridine, toluene and eugenol is 0.5-0.8:0.02-0.05:30-35:1-2; A2, N-bromosuccinimide and dimethylformamide are mixed, then benzoyl peroxide is added, stirred for 1-2h, intermediate product 1 is added, heated with stirring for 2-4h, then isopropanolamine is added, heated with stirring for 60-80min, then L-cysteic acid is added, heated with stirring for 2-3h, and distilled under reduced pressure to obtain intermediate product 2; wherein, the mass ratio of N-bromosuccinimide, dimethylformamide, benzoyl peroxide, intermediate product 1, isopropanolamine and L-cysteic acid is 15-25:130-150:1-2:30-40:20-25:10-15; A3. Mix the intermediate product 2 with the tetrahydrofuran solution, stir for 10-15 min, add tetrabutylammonium fluoride, heat and stir for 25-40 min, and distill under reduced pressure to obtain a functional product; wherein the mass ratio of the intermediate product 2, the tetrahydrofuran solution and the tetrabutylammonium fluoride is 10-15:50-60:2-4.
4. The coolant according to claim 1, characterized in that: The functional additive is prepared by mixing polydimethylsiloxane and a diesel flash point enhancer in a mass ratio of 0.5-0.8:4-5.
5. The coolant according to claim 1, characterized in that: The thermally conductive filler is prepared by the following method: The graphene oxide is dispersed in deionized water, ultrasonically dispersed for 15-25 minutes, zinc acetate and p-phenylenediamine are added, stirred for 5-8 minutes, sodium hydroxide is added to adjust the pH to obtain a mixed solution, the mixed solution is heated to 150-180° C., kept warm for 12-20 hours, cooled to room temperature, centrifuged, washed, and dried to obtain a thermal conductive filler.
6. The coolant according to claim 5, characterized in that The mass ratio of the graphene oxide, zinc acetate, p-phenylenediamine, sodium hydroxide and deionized water is 8-12:2-4:0.5-0.8:0.05-0.1:60-75.
7. A method for preparing a coolant according to any one of claims 1 to 6, characterized in that: The following steps are involved: The antioxidant, functional additive, thermal conductive filler and propylene glycol are mixed, and then synthetic oil and rust inhibitor are added, stirred for 25-35 minutes, and then a solubilizer is added, and stirred for 30-45 minutes to prepare a coolant.
8. Use of the coolant according to any one of claims 1 to 6 in an immersion liquid cooling system.